Overview of funding for construction craft skills training in Sub-Saharan Africa: A case study of Zambia - Muya, Mundia; Price, A. D F; Edum-Fotwe, F. T. (Construction Management and Economics, 2006)
The wealth of any nation is ultimately based on its human resource or social capital. Education and training are the primary vehicles of developing this resource. Funding of formal construction craft skills training at trade institutions in Sub-Saharan Africa (SSA) is examined, using Zambia as a country case study. The data in the research were collected via semi-structured questionnaire interviews directed at government financed trades training schools offering construction programmes in Zambia. Results of the research show that formal construction craft skills training in Zambia has not been adequately funded over the years resulting in: ill-qualified low numbers of poorly remunerated teaching staff; poorly maintained infrastructure and workshop facilities not well equipped for teaching purposes; and out-dated curricula of construction craft programmes. A wide range of measures is required to improve funding for construction craft skills training. These include: increased training regulation and co-ordination by government, development of efficient and effective funding mechanisms that involve employers of crafts-persons, and training provision frameworks that encourage increased involvement of private training providers. © 2006 Taylor & Francis.
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Zambia; CA:AandC; CCZ:Zambia; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:regulation; F:teaching; P:construction; P:crafts; P:measurement; P:mechanic; P:social; R:case study; R:interview; R:questionnaire; T:Training; Z:Construction craft skills; Z:Sub-Saharan Africa; Z:Training; publicImportV1